The role of zoophilous flies in the spread of zoonoses in cattle breeding farms of the Ivanovo region and measures to combat them - S. V. Egorov; E. N. Kryuchkova; B. G. Abalikhin; E. A. Sokolov (Российский паразитологический журнал, 2022)
The purpose of the research is to study the fauna of zoophilous flies on the territory of the farms of the Palekh district of the Ivanovo region, to determine the comparative effectiveness of insecticidal preparations and the duration of their action; establish the role of zoophilous flies in the spread of helminth eggs and protozoan oocysts.Materials and methods. The faunistic collection of zoophilous flies was carried out in calf dispensaries of livestock farms in the farms of the Palekh district of the Ivanovo region. The species of zoophilic flies was determined at the Department of Infectious and Parasitic Diseases of the Ivanovo State Agricultural Academy. The comparative effectiveness of insecticidal preparations was carried out.Results and discussion. The fauna of zoophilic flies on cattle farms in the farms of the Ivanovo region of the Palekh district is represented by three families: Muscidae (92.78%), Calliphoridae (1.16%), Scatophagidae (5.69%). They are equally contaminated with eggs of pathogens of helminthoses and oocysts of pathogens of protozooses, and their role in the spread of helminthosis and protozoosis is determined by the index of dominance in the fauna of livestock buildings. The fastest effect of acute insecticidal action was observed in the drug with AD imidacloprid – 4 min. after contact of insects with treated surfaces of objects. In preparations with AD, thiamethoxam and cypermethrin showed insecticidal properties after 8 min. The longest insecticidal effect was observed in the drug with AD imidacloprid; it was 13 days, while for drugs with DV thiamethoxam and cypermethrin - a little more than half of this period.